The Relationship of Teacher Competency With Student Development Resilience: Reflection of 21st Century Learning During Pandemic - Parahita, Bagas Narendra (Universitas Muhammadiyah Mataram, 2022)
The competence of teachers in 21st century learning is important in order to keep up with the times. A review of qualitative research using a phenomenological approach in this study was carried out in order to be able to adjust the learning experience during the COVID-19 pandemic experienced by the teachers. This research was conducted on high school teachers with a sample of 8 teachers spread across several areas on the island of Java to obtain the complexity of the data results and as a response to the process of adapting research developments during the pandemic with a semi-structured interview process both offline and online utilizing various online platforms. The results of the study showed that teacher competence is closely related to the development of students and 21st century learning during the pandemic. The aspects that have strong relationship are cognitive competencies that require dynamic educators to provide opportunities for students to develop their potential, social competencies possessed by teachers are needed to improve interactive and networked student communication, teacher personality competencies are still needed to strengthen student character, and teachers with professional competence encourage teachers to be proactive in developing skills to strengthen the quality of student learning outcomes.